The Influence of Brand Image, Price and Product Quality on the Decision to Purchase Oppo Mobile Phones in Tangerang City People - Ariyanto, Aris; Sudarsono, Agus; Wijayanti, Kiki Dwi (International Journal of Business and Applied Economics, 2025)
A survey by IDC revealed that Indonesia's smartphone shipments dropped by 6.3% year-on-year in Q2 2023, with Oppo experiencing the largest decline of 19.8%, selling 1.6 million units. This study examines the influence of brand image, price, and product quality on Oppo smartphone purchasing decisions in Tangerang City using a quantitative descriptive approach with 230 participants analyzed via Partial Least Squares (PLS). Results show that brand image, price, and product quality, individually and collectively, significantly influence purchasing decisions. Recommendations include enhancing Oppo's brand image through software quality and design, revising pricing strategies, improving battery performance, and streamlining the purchasing process to strengthen competitiveness.